The role of spiral arms in Milky Way star formation. Issue 2 (26th June 2018) - Ragan, S E; Moore, T J T; Eden, D J; Hoare, M G; Urquhart, J S; Elia, D; Molinari, S
ABSTRACT: What role does Galactic structure play in star formation? We have used the Herschel Infrared Galactic Plane Survey (Hi-GAL) compact-clump catalogue to examine trends in evolutionary stage over large spatial scales in the inner Galaxy. We examine the relationship between the fraction of clumps with embedded star formation (the star-forming fraction, or SFF) and other measures of star formation activity. Based on a positive correlation between SFF and evolutionary indicators such as the luminosity-to-mass ratio, we assert that the SFF principally traces the average evolutionary state of a sample and must depend on the local fraction of rapidly evolving, high-mass young stellar objects. The spiral-arm tangent-point longitudes show small excesses in the SFF, though these can be accounted for by a small number of the most massive clusters, just 7.6 per cent of the total number of clumps in the catalogue. This suggests that while the arms tend to be home to the Galaxy's massive clusters, the remaining 92.4 per cent of Hi-GAL clumps in our catalogue do not show an enhancement of star formation within arms. Globally, the SFF is highest at the Galactic mid-plane and inner longitudes. We find no significant trend in evolutionary stage as a function of position across spiral arms at the tangent-point longitudes. This indicates that the angular offset observed between gas and stars, if coordinated by a density wave, is not evident at the clump phase; alternatively, the onset of star formation is not triggered by the spiral density wave.